2013
DOI: 10.1039/c3cp50896j
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical effects on the aggregation and biological properties of the fibril-forming peptide [KIGAKI]3 in membranes

Abstract: Single D-amino acid substitutions can be used to suppress or slow down the aggregation of peptides into β-sheeted assemblies compared to the respective L-amino acids. Here, we investigate the influence of local stereochemistry in the model peptide [KIGAKI]3-NH2, which is known to form amyloid-like fibrils. To find out whether aggregation plays a role in various biologically relevant functions that involve peptide-lipid interactions, we studied the antimicrobial, hemolytic and fusogenic activities of this amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 39 publications
(81 reference statements)
1
33
0
Order By: Relevance
“…Anionic lipids are known to be the main components of bacterial membranes, which contain in many cases well over 50% PG50. Furthermore, a negative charge is necessary to attract the water-soluble cationic peptides electrostatically to the vesicles4851. Leakage curves were measured at different P/L ratios, over 10 minutes after addition of the vesicle suspension to the peptide solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anionic lipids are known to be the main components of bacterial membranes, which contain in many cases well over 50% PG50. Furthermore, a negative charge is necessary to attract the water-soluble cationic peptides electrostatically to the vesicles4851. Leakage curves were measured at different P/L ratios, over 10 minutes after addition of the vesicle suspension to the peptide solution.…”
Section: Resultsmentioning
confidence: 99%
“…Small unilamellar vesicles (SUVs) for CD samples were generated by sonication in a high-power ultrasonic bath with a beaker-shaped sonotrode (UTR 200, Hielscher, Germany). CD spectra were recorded on a J-815 spectropolarimeter (JASCO, Groß-Umstadt, Germany) between 260 and 185 nm at 0.1-nm intervals, using 1-mm quartz glass cells (Suprasil; Hellma, Müllheim, Germany) at 20°C, as reported previously51. The peptides were measured at 20°C in 10 mM sodium phosphate buffer (pH 7.0) and at 30°C in lipid vesicles composed of DMPC/DMPG (3:1).…”
Section: Methodsmentioning
confidence: 99%
“…This seemingly simple change can cause significant effects in a system altering its conformational and thus functional and biological properties. The amphiphilic membrane‐active model peptide [KIGAKI] 3 ‐NH 2 , is used to investigate this effect of the reversal of an amino acids stereochemistry, as it is known to form amyloid‐like fibrils . This peptide has been shown to exhibit potent activity against various bacteria compared to that of amphiphilic α‐helices .…”
Section: Application Of Rigid‐linear Linkers In Small Molecule Drugsmentioning
confidence: 99%
“…Aggregation is often associated with the transition of an intrinsically unstructured peptide into oligomeric β-sheets in a concentration and time dependent manner. We have recently used the model peptide [KIGAKI] 3 to examine this process and characterize its typical 19 F-NMR signature [40], [89]. Self-assembly of this system in membranes [40], [66] leads to formation of fibrils that are similar to amyloid consisting of hydrogen-bonded cross-β-strands [32][34], [36], [90].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time - and seemingly contradictory at first sight - it has been reported that D - amino acids can also be used to prevent the aggregation of peptides [39], [40], [89]. This effect is not attributed to equilibrium between helix and unfolded state (as in TP10 or Aβ), but instead to the self-assembly of already unfolded peptides (from the β-stranded KIGAKI family) into aggregated fibrils.…”
Section: Discussionmentioning
confidence: 99%